2018
DOI: 10.31142/ijtsrd18611
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Employee Loyalty Towards BSMED, Bharathiar University, Coimbatore, Tamil Nadu, Indiaal Culture on BSMED, Bharathiar University, Coimbatore, Tamil Nadu, Indiaal Performance Reference to Private Banks In Coimbatore City

Abstract: Organizational Performance Management and Measurement is one of the most popular terms in today's business. The idea of managing organizational performance is being widely accepted and adopted all over the world. It spread rapidly from the private sector to the public sector in the developed world and has recently found its way in many developing countries. Organizational performance is generally assessed with financial indicators such as return on investment or profit per share. This narrowness of criteria fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Positive skewness and platykurtic distribution were observed for plant height and leaf length indicating that the genes are governed by complementary gene action. Tamil (2012) and Suresh (2014) have also reported leptokurtic distribution and negative skewness for cob length which indicated that the trait is controlled by less number of genes. In BC 2 F 1 generation, a wide range of variation was observed for plant height, cob length and the number of kernels per row and a narrow range of variation was observed for days to tasseling and days to silking.…”
Section: Resultsmentioning
confidence: 99%
“…Positive skewness and platykurtic distribution were observed for plant height and leaf length indicating that the genes are governed by complementary gene action. Tamil (2012) and Suresh (2014) have also reported leptokurtic distribution and negative skewness for cob length which indicated that the trait is controlled by less number of genes. In BC 2 F 1 generation, a wide range of variation was observed for plant height, cob length and the number of kernels per row and a narrow range of variation was observed for days to tasseling and days to silking.…”
Section: Resultsmentioning
confidence: 99%
“…A Study by Suresh and Jaleel (2015) on the impact of Employee Empowerment on Organizational Performance. A Case of Automobile Industry in Chennai City of Tamil Nadu in India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If the above-mentioned problems exist at the firm, employee performance decreases not due to a lack of relevant knowledge, skills and attitude, but because of the above-mentioned hurdles. To make training effective and to make sure the positive effect of training on employee performance these elements be taken into consideration (Suresh and Jaleel, 2015) Bartel (1994) and Bester Stander and Van (2015), reported that there is a positive correlation between effective training programs and employee productivity. However, to make it possible, it is the responsibility of the managers to find the factors that hinder training program effectiveness and should take necessary measures to neutralize their effect on employee performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Organizational Commitment is of significant research interests because of the relationship between commitment and desirable organizational outcomes such as creativity and innovativeness (Ali. & Puah, 2017;Battistelli, Odoardi, Vandenberghe, Di Napoli, & Piccione, 2019;Li & Zheng, 2014) increased job performance (Kim et al, 2018;Sungu et al, 2019) employee loyalty (Suresh & Mahalingam, 2018) and job satisfaction (Sait, 2017;Luz, Paula, & Oliveira, 2018). Committed employees help create an organization"s competitive advantage and are motivated to give their best to the organization.…”
Section: Organizational Commitment (Oc) and Job Performance (Jp)mentioning
confidence: 99%